Explaining the favorite-longshot bias: Is it risk-love or misperceptions? - Erik Snowberg; Justin Wolfers (Institute for the Study of Labor (IZA), 2010)
The favorite-longshot bias describes the longstanding empirical regularity that betting odds provide biased estimates of the probability of a horse winning - longshots are overbet, while favorites are underbet. Neoclassical explanations of this phenomenon focus on rational gamblers who overbet longshots due to risk-love. The competing behavioral explanations emphasize the role of misperceptions of probabilities. We provide novel empirical tests that can discriminate between these competing theories by assessing whether the models that explain gamblers' choices in one part of their choice set (betting to win) can also rationalize decisions over a wider choice set, including compound bets in the exacta, quinella or trifecta pools. Using a new, large-scale dataset ideally suited to implement these tests we find evidence in favor of the view that misperceptions of probability drive the favorite-longshot bias, as suggested by Prospect Theory.
Keywords: D03; D49; G12; L83; 330; Pricing under risk; probability weighting; compound lotteries; favorite-longshot bias; Glücksspiel; Entscheidung bei Unsicherheit; Bias; Prospect Theory; Wahrnehmung; Risikopräferenz; Test